2005
DOI: 10.1038/sj.jhh.1001965
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between pulse wave velocity, augmentation index, pulse pressure and left ventricular function in chronic heart failure

Abstract: Pulse wave velocity (PWV), the carotid augmentation index (AIx), and pulse pressure (PP) may be prognostic factors in heart failure, but the possible influence of the ejection fraction (EF) and other simple haemodynamic variables on them has not been investigated in this setting. Noninvasive methods were used to measure carotid-radial (CR), carotid-femoral (CF) PWV and AIx, and brachial PP, in 135 consecutive patients with stable symptomatic chronic heart failure. The patients were divided into two groups, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
35
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 43 publications
7
35
0
3
Order By: Relevance
“…However, in contrast to those results, we found an increase in Tr of the pressure wave, indicating a decrease in PWV, and an increase in pulse pressure amplification, which together imply a decrease in arterial stiffness and is consistent with the measured decrease in augmented pressure and AI a . Our results are supported by the results of Tartière et al, 33 which involved patients with a similar EF (mean LVEF 24Ϯ9% among study patients with reduced EF) and which showed a decrease in the effects of wave reflection on AoPW. These pressure changes result from altered ventricular/vascular coupling.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, in contrast to those results, we found an increase in Tr of the pressure wave, indicating a decrease in PWV, and an increase in pulse pressure amplification, which together imply a decrease in arterial stiffness and is consistent with the measured decrease in augmented pressure and AI a . Our results are supported by the results of Tartière et al, 33 which involved patients with a similar EF (mean LVEF 24Ϯ9% among study patients with reduced EF) and which showed a decrease in the effects of wave reflection on AoPW. These pressure changes result from altered ventricular/vascular coupling.…”
Section: Discussionsupporting
confidence: 82%
“…Only one previous study reported a decrease in arterial stiffness and PWV similar to our findings; this was the study by Tartière et al, 33 performed in patients with severe LVSD and reduced mean arterial pressure. Because the activities of the LV and peripheral arterial system are interactive (ventricular/vascular coupling), the decrease in arterial stiffness and PWV may be the result of a decrease in mean arterial pressure in response to reduced cardiac output and LV afterload.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Prior studies have shown that mean AIx in HFrEF patients is 21%, 18 and that AIx is reduced (in absolute units) by 8% with enalapril, 12 20% with nitrates, 13 and 9% with spironolactone. 14 The goal in the active treatment arm was to reduce AIx to 0%.…”
Section: Sample Size Considerationsmentioning
confidence: 99%
“…7 The epidemiology, 8 genetic associations 9 and prognostic implications 10 of PWV (and arterial stiffness) have also been reported as has the relationship to haemodynamics, 11 cardiac structure and function. 12,13 Thus, it is increasingly important to have accurate and reproducible methods to assess PWV. In this issue of the Journal of Human Hypertension, Salvi and co-workers 14 demonstrate the reproducibility and reliability of PWV measured by three frequently used devices: the Complior and the PulsePen, both of which determine aortic PWV as the delay between carotid and femoral pressure wave, and the PulseTrace, which estimates the Stiffness Index by analysing photoplethysmographic waves acquired on the fingertip.…”
mentioning
confidence: 99%